PERSEPSI TOKOH AGAMA TERHADAP UANG MAHAR YANG DIJADIKAN HIASAN DALAM AKAD NIKAH DI KECAMATAN SUBAH KABUPATEN SAMBAS - Khasanah, Uswatun; Hasan, Muhammad; Muzamil, Sadulloh (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
The purpose of this research is to find out: 1) Perceptions of religious figures on the dowry of money that is used as decoration for ever and temporarily. 2) The perception of religious leaders on the forms of dowry that can be used as decoration in the marriage contract. 3) Perceptions of religious leaders on the originality of the dowry of money used as decoration in the marriage contract. The research method used in this study is a qualitative research method, with an empirical approach and using field research. The primary data sources for this study were religious leaders in Subah District, Sambas Regency. Secondary data sources are the Qur'an, hadith, theses, journals and books. Data collection techniques used were interviews and documentation. Data collection tools were recorders and interview guides. The data analysis technique used was data reduction, data exposure and drawing conclusions. Checking the validity of the data by using the source triangulation. This study concludes that: 1) Regarding the perception of religious figures on the dowry of money that is used as decoration in the long term and meanwhile there are 3 opinions, namely agree, neutral and disagree. 2) Perceptions of religious leaders on the forms of dowry that can be used as decoration, there are 3 forms, namely money, a set of prayer tools and jewelry, but among the three money is the most frequently used. 3) Perceptions of religious figures on the originality of the dowry of money used as decoration in the marriage contract, there are 2, namely real money and play money.